2012
DOI: 10.1177/1479972312464245
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early adherence to tiotropium in chronic obstructive pulmonary disease

Abstract: Tiotropium is an innovative intervention in chronic obstructive pulmonary disease (COPD). Early adherence to tiotropium remains inadequately explored, notably time from initiation to discontinuation (persistence). In patients with COPD, the factors associated with the risk of discontinuing the treatment with tiotropium within 12 months following initiation were identified (12-month persistence). Claim databases from the French Social Security were used. A random sample of patients (aged 50-80 years) who initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…This result was similar to those found in the USA and the Netherlands, where similar definition of adherence and exlusion criteria were implemented. Different levels of adherence to Tiotropium that were found in other studies may be attributed to the use of different measures of adherence and differences in baseline COPD diagnosis and disease severity of study population. Unexpectedly, our study demonstrated no significant difference between adherent and non‐adherent patient with regard to age, gender, disease severity and comorbidities that were found previously to be associated with adherence in COPD .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…This result was similar to those found in the USA and the Netherlands, where similar definition of adherence and exlusion criteria were implemented. Different levels of adherence to Tiotropium that were found in other studies may be attributed to the use of different measures of adherence and differences in baseline COPD diagnosis and disease severity of study population. Unexpectedly, our study demonstrated no significant difference between adherent and non‐adherent patient with regard to age, gender, disease severity and comorbidities that were found previously to be associated with adherence in COPD .…”
Section: Discussionmentioning
confidence: 61%
“…This result was similar to those found in the USA and the Netherlands, where similar definition of adherence 31,32 and exlusion criteria 32 were implemented. Different levels of adherence to Tiotropium that were found in other studies [28][29][30]33 may be attributed to the use of different measures of adherence and differences in baseline COPD diagnosis and disease .143 † Adherent patients were defined as those whose proportion day covered (PDC) of Tiotropium was ≥80%. ‡ LABA and/or ICS refers to inhaled corticosteroids therapy (R03BA) and/or other long-acting beta-agonists, including salmeterol (R03AC12), formoterol (R03AC13), indacaterol (R03AC18), salmeterol and fluticasone (R03AK06), and formoterol and budesonide (R03AK07).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations